Evaluation of Separating Process for Different Materials by Thermal Stress Cleaving Technique - Mohd Saman, Alias; Furumoto, Tatsuaki; ., . (International Journal of Engineering and Technology, 2018)
This paper aims to evaluate the separating process of brittle materials by thermal stress cleaving technique. This process is suitable for separating thin brittle materials such as sapphire and silicon wafer, which are sensitive to force.Â Both materials were used largely in microelectronics, solar cells and micro-mechanical industries that require precise machining. Finite element method was used to evaluate a steady state thermal stress by considering the temperature transient during laser irradiation process. The heat source was assigned according to the laser energy absorption characteristics of the materials. Stress intensity factor was analyzed to determine the starts of separation process. The results show that CO2 laser energy was absorbed on the surface of the sapphire material as compared proportionated absorption of Nd:YAG laser energy on silicon material. Due to thermal stress generated by the laser beam, material separation was start. Fracture begins at the bottom surface of sapphire wafer compared to fracture initiation at the prepared groove for silicon wafer. The material separation can be controlled when it begins at the groove. Hence, better surface finished can be achieved.Â Â Â Â Â Â Â Â Â